2017
DOI: 10.1097/ta.0000000000001519
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the cardiac box

Abstract: Therapeutic/care management, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…16,17 Recent studies have provided further details regarding the influence of the mechanism of injury and the number of wounds on cardiac injury. [18][19][20] To rule out a cardiac injury in the initial assessment, eFAST plays a prominent role in the initial patient assessment. 21,22 A systematic review and meta-analysis published in February 2021 concluded that the use of ultrasound was 79% sensitive and 92% specific for detecting occult penetrating cardiac injuries in hemodynamically stable patients with PTI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Recent studies have provided further details regarding the influence of the mechanism of injury and the number of wounds on cardiac injury. [18][19][20] To rule out a cardiac injury in the initial assessment, eFAST plays a prominent role in the initial patient assessment. 21,22 A systematic review and meta-analysis published in February 2021 concluded that the use of ultrasound was 79% sensitive and 92% specific for detecting occult penetrating cardiac injuries in hemodynamically stable patients with PTI.…”
Section: Discussionmentioning
confidence: 99%
“…Although cardiac box wounds are potentially acknowledged as cardiac injuries, the evidence to support this association is lacking 16,17 . Recent studies have provided further details regarding the influence of the mechanism of injury and the number of wounds on cardiac injury 18–20 . To rule out a cardiac injury in the initial assessment, eFAST plays a prominent role in the initial patient assessment 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Historically, a penetrating wound to the “cardiac box” (between midclavicular lines from clavicles to tip of xiphoid process) or any other transmediastinal wound was considered to be a likely cause of a cardiac injury. Of interest, one recent clinical and autopsy study documented that changing the cardiac box from the anterior to posterior midline on the left side had a positive predictive value of 41% with a sensitivity of 90% for a cardiac injury 10 . Therefore, the definition of the cardiac box is likely to change in future publications 11,12 …”
Section: Presentation Diagnosis and Management In The Emergency Depar...mentioning
confidence: 99%
“…62 Abnormalities included the following: pericardial effusion (9), abnormal wall motion (8), decreased ejection fraction <45% (8), intramural thrombus (4), valve injury (4), cardiac enlargement (2), conduction abnormality (2), left ventricular pseudoaneurysm (1), right ventricular aneurysm (1), and septal defect (1). No patient underwent a reoperation, although 11 were under medical management (10) or required cardioversion (1). There were two patients with late deaths (injuries to left ventricle and right ventricle, respectively), but the causes were not listed.…”
Section: Indications For Cardiopulmonary Bypassmentioning
confidence: 99%
See 1 more Smart Citation